Chemical Constituent of Murraya Paniculata (Rutaceae) and Their Biological Activities - Syed Abd. Azziz, Saripah Salbiah (1998)
An investigation on the plant of Murraya paniculata, employing extraction of the leaves and stem barks and various chromatographic isolation techniques have been used. The structure of the compounds were elucidated by using spectroscopic techniques such as IR, NMR, MS and also by comparison with the previous work. Extraction and isolation work of the leaves and stem barks of Murraya paniculata collected from Lenggong, Perak yielded gardenin E (28), 3',4',5,5', 7-pentamethoxyflavone (29), 3',4',5,5', 7,8-hexamethoxyflavone (30), gardenin A (31), sterol mixtures (32), 3',4',5,5',7-pentamethoxyflavanone (33) and gardenin C (34). Further study on the leaves of the same plant collected from different location in lpoh, Perak afforded four known coumarins ; auraptene (36), gleinadiene (37), 5,7-dimethoxy-8-(3-methyl-2-oxo-butyl)coumalin (38) and toddalenone (39). The antibacterial and antifungi activities test were also carried out on elUde PE, CHCh and MeOH extracts of the leaves and stem barks and also towards pure compounds. This antibacterial activity was tested using the 'disk Diffusion' method. One gram positive bacteria (Baccilus cereus) and four fungi (Aspergillus ochraceous, Saccharomyces lipolytica, Saccharomyces cerevisiae dan Candida lipolytica) were selected for this test. Chloroform extract of Murraya paniculata gave the highest average zone of inhibition, indicating the degree of its sensitivity. Meanwhile compound (37) showed moderate degree of toxicity towards the bacteria.